Species diversity, abundance and damaged caused by rats in oil palm plantation in West and Central Sulawesi, Indonesia - Muhammad Ikhsan; SWASTIKO PRIYAMBODO; ALI NURMANSYAH; HENNY HENDARJANTI; BANDUNG SAHARI (Society for Indonesian Biodiversity, 2020)
Abstract. Ikhsan M, Priyambodo S, Nurmansyah A, Hendarjanti H, Sahari B. 2020. Species diversity, abundance and damaged caused by rats in oil palm plantation in West and Central Sulawesi, Indonesia. Biodiversitas 21: 5632-5639. Oil palm is one of the plantation commodities which has an important role in Indonesia’s economy. Indonesia is the largest producer and exporter of oil palm in the world with its export value capable of supplying 55.78% of global consumption. Rats are wild animals that are important pests for human life, both in agriculture plantations and urban areas. Rats can damage crops at various stages of plant growth. This study was aimed to determine the species abundance of rats in oil palm plantations, calculate the severity of crop damage due to rats infestation. Three blocks of mature plants were used in OC and OH plantation blocks were used to calculated, crop damage caused by rats, Identify the species of rats, and estimated rats abundance. The results of these studies showed there were four species of rats found in the oil palm plantation, namely Rattus tiomanicus, R. tanezumi, Rattus sp, and Maxomys hellwaldii. However, only R. tiomanicus and R. tanezumi were dominant species. There were significant differences in the number of, sex, and body weight between R. tiomanicus and R. tanezumi. The OC 12 block had the lowest infestation intensity than the other blocks since it was well maintained. The OH 02 block had the highest infestation intensity, infestation area, and abundance due to a lack of maintenance.